Socioeconomic differences in incident metabolic syndrome in adults: the mediation of health behaviors. (30th September 2020) - Hoveling, L A; Liefbroer, A C; Bültmann, U; Smidt, N
Abstract: Introduction: The incidence of metabolic syndrome (MetS) strongly varies by socioeconomic status (SES). Health behaviors could be one of the mechanisms explaining the SES-MetS relationship, but little is known about their mediating role. This study aims to longitudinally asses the association between SES measures, education, income and occupational prestige, and incident MetS and whether the associations are mediated by health behaviors, including physical activity, smoking, alcohol drinking and diet quality. Methods: A subsample of the adult Lifelines Cohort Study, including 85, 910 participants without MetS at baseline was used. MetS was measured at the second assessment (follow-up time 3.8 years) defined according to the NCEP-ATPIII criteria. Direct associations between SES, health behaviors and incident MetS were estimated using multivariable logistic regression analyses. The mediating percentages of health behaviors explaining the associations between SES and incident MetS were estimated using the Karlson-Holm-Breen method. Analyses were independent of age, sex, the other SES measures and follow-up time. Results: Education (OR 0.92, 99% CI: 0.91-0.94) and occupational prestige (OR 0.94, 99% CI: 0.91-0.97) were inversely associated with MetS. Income was not associated with MetS. Health behaviors explained only partly (13.8%) the association between education and MetS, with smoking as the strongest mediating factor (8.6%). Health behaviors played a minor role (2.7%) in explaining occupational MetS differences, with physical activity as the strongest suppressing factor (-10.4%). Conclusions: Individuals with more years of education or a higher occupational prestige showed a decreased risk of developing MetS. This was mainly because of non-smoking, less often excessive alcohol drinking and a higher diet quality; however, they were more often physically inactive. Key messages: Education and occupational prestige are inversely associated with MetS incidence. Health behaviors explain a small part of the SES – MetS incidence pathway, with smoking as the largest contributor.